lmplementation of a national regulatory framework for drinking water safety plans in Uruguay - Jose M. P. Vieira; Sandra Rodríguez; Paula Suarez; Ricardo Kramer (IWA Publishing, 2023)
The establishment of national strategic frameworks for systematic scaling-up of water safety plans (WSPs) implementation needs to overcome major constraints: lack of legislation and policies, and the need for appropriate monitoring tools. In 2018, the Uruguayan regulator for energy and water services promulgated a regulation intended to ensure an ambitious and pragmatic strategy that supports and promotes WSP implementation and auditing at a national scale. The goal is to have all drinking water supply systems with their WSP implemented by 2030. For this, a demanding schedule was recommended considering the size of the drinking water supplies: (i) large systems serving more than 2,000 inhabitants and (ii) small and very small systems serving fewer than 2,000 inhabitants. A mandatory verification through internal and external audits was also established. This work describes the legal and regulatory framework as well as the challenges and opportunities that open up for the generalization of WSP implementation in Uruguay. Despite the impact of COVID-19 on working conditions for water suppliers, as for the year 2022, WSPs have been successfully implemented in 94 water systems serving more than 2.4 million people. Results of successful implementation and auditing processes are presented and discussed covering methods and outcomes. HIGHLIGHTS Mandatory regulation plays a pivotal role in the nationwide adoption of WSP.; WSP implementation contributes to achieving targets of SDG 6.; Regulation provides Uruguayan managerial and operational mechanisms for effective supply of safe drinking water.; Auditing has proven to be an essential component for ensuring the effective operation of WSP.; WSP implementation and auditing in Uruguay are currently at an advanced stage.;